Organizing Corporate Social Responsibility in Small and Large Firms: Size Matters - Baumann-Pauly, Dorothée; Wickert, Christopher ca. 20./21. Jh.; Spence, Laura J. 1968-; Scherer, Andreas Georg 1964- (2013)
Based on the findings of a qualitative empirical study of corporate social responsibility (CSR) in Swiss MNCs and SMEs, we suggest that smaller firms are not necessarily less advanced in organizing CSR than large firms. Results according to theoretically derived assessment frameworks illustrate the actual implementation status of CSR in organizational practices. We propose that small firms possess several organizational characteristics that are favorable for promoting the internal implementation of CSR-related practices in core business functions, but constrain external communication and reporting about CSR. In contrast, large firms possess several characteristics that are favorable for promoting external communication and reporting about CSR, but at the same time constrain internal implementation. We sketch a theoretical explanation of these differences in organizing CSR in MNCs and SMEs based on the relationship between firm size and relative organizational costs.
Keywords: Small- and medium-sized enterprises (SME); Organizational cost; Multinational corporations (MNC); Firm Size; Corporate social responsibility (CSR)